2013
DOI: 10.1007/978-3-642-41098-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Technical Study on the Effect of Trust and Context When Choosing WiFi Names

Abstract: Abstract. We study trust and context as factors influencing how people choose wireless network names. Our approach imagines the mindset of a hypothetical attacker whose goal is to ensnare unsuspecting victims into accessing dishonest WiFi access points. For this purpose, we conducted an online survey. We used two separate forms. The first form asked a random group of participants to rate a list of wireless names according to their preferences (some real and others purposely made-up) and afterwards with implied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…More sophisticated evaluation of trust may take into account other aspects, e. g., current location of an employee [27]. Strength r of a network can be associated with the number of bars showing the strength of the signal, and one may expect that people would chose networks with high signal strength.…”
Section: Selection Of a Wi-fi Network With Mavtmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated evaluation of trust may take into account other aspects, e. g., current location of an employee [27]. Strength r of a network can be associated with the number of bars showing the strength of the signal, and one may expect that people would chose networks with high signal strength.…”
Section: Selection Of a Wi-fi Network With Mavtmentioning
confidence: 99%
“…Participants were asked to rank networks according to the order in which they would try to connect to the networks, assuming they have the password to access every available Wi-Fi. The network names were composed from randomly generated alphabetic characters and numbers to avoid bias due to perceived familiarity of network names (see [27] for a study of this effect). The names of screenshots encode the manner of presentation, which relates closely to the criteria to be used in the MAVT model presented in Section 5.2.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…We used randomly generated network names to avoid biasing the results due to perceived familiarity with the network (see work on this by [13]. )…”
Section: B Study Materialsmentioning
confidence: 99%
“…1: Geo-distribution of the collected SSIDs in Sydney studied the names of user devices that are sending mDNS in a WiFi network and found that 59% of the device names contained real names and 17.6% contained both first name and last name. Ferreira et al [15] investigated the effect that trust and context have on users when choosing wireless networks. For example, it was shown that users tend to connect to the networks known to them or have connected in the past, despite not completely trusting them.…”
Section: Related Workmentioning
confidence: 99%
“…Various aspects on how users name their smart devices has been also explored [10], [11], [12], [13], [14], [15]. O'Neill et al [10] studied Bluetooth names of 1,701 devices and showed that 42% devices tend to use default names given by the manufacturer.…”
Section: Related Workmentioning
confidence: 99%